Not missing at random: Missing data are associated with clinical status and trajectories in an electronic monitoring longitudinal study of bipolar disorder - Halabi, Ramzi; Mulsant, Benoit H; Alda, Martin; DeShaw, Alexandra; Hintze, Arend; Husain, Muhammad I; O'Donovan, Claire; Patterson, Rachel; Ortiz, Abigail (Journal of psychiatric research, 2024)
There is limited information on the association between participants' clinical status or trajectories and missing data in electronic monitoring studies of bipolar disorder (BD). We collected self-ratings scales and sensor data in 145 adults with BD. Using a new metric, Missing Data Ratio (MDR), we assessed missing self-rating data and sensor data monitoring activity and sleep. Missing data were lowest for participants in the midst of a depressive episode, intermediate for participants with subsyndromal symptoms, and highest for participants who were euthymic. Over a mean ± SD follow-up of 246 ± 181 days, missing data remained unchanged for participants whose clinical status did not change throughout the study (i.e., those who entered the study in a depressive episode and did not improve, or those who entered the study euthymic and remained euthymic). Conversely, when participants' clinical status changed during the study (e.g., those who entered the study euthymic and experienced the occurrence of a depressive episode), missing data for self-rating scales increased, but not for sensor data. Overall missing data were associated with participants' clinical status and its changes, suggesting that these are not missing at random.
Keywords: Young Adult; Female; bipolární porucha; mladý dospělý; dospělí; Adult; Humans; ženské pohlaví; longitudinální studie; mužské pohlaví; Male; lidé; Longitudinal Studies; lidé středního věku; zpráva o sobě; Middle Aged; Bipolar Disorder; Self Report